Prospects for the use of inulin and its modifications in the food, cosmetic and pharmaceutical industries - Skorodumov A. S.; Nesterov E. D.; Gorn D. S.; Barkanov A. V.; Shanenko E. F. (Vestnik MGTU)
The paper contains a review of modern data on the use of the polysaccharide inulin and its modifications in various industries. Data on the use of native inulin in various food technologies have been presented. Its use in the production of bakery products, cereal products, various types of dairy products, meat and flavoring products has been shown. In these product categories, inulin is used as a stabilizer, texturizer, water-retaining agent, emulsifier and prebiotic component of the recipe. In bakery products, inulin has a positive effect on the rheological properties of the dough, increases the amount of bound moisture, reduces water activity, slows down the staling process, which allows to increase the shelf life of finished products. In cereal products and bars, inulin is actively used in the production of prebiotic products, since it acts as a dietary fiber. In dairy products, inulin allows to reduce fat content, since it has the ability to impart a creamy taste to products, improves the rheological properties of dairy products, in probiotic dairy products, inulin improves the state of the probiotic microbial culture. In meat and flavoring products, inulin increases the yield of finished products due to the water-holding capacity, improves the stability of emulsions and allows to obtain products with reduced fat content due to partial replacement of fats in recipes. The prospect of using inulin to obtain modifications with various properties, such as cross-linked inulin, hydrophobic inulin, inulin esters, and cycloinulin has been shown. A description of examples of inulin modifications and the possibility of their application in the food, cosmetic, pharmacological industries and in nanotechnology has been given.